Effect Foot Soak Using Warm Water Mixed with Salt and Lemongrass to Decrease Pressure in Hypertension Patients in the Podorejo Ngaliyan - Priharyanti Wulandari (University of Muhammadiyah Malang, 2016)
The incidence of hypertension in the region Podorejo RW 8 Ngalliyan in 2014 as many as 85 people, increase in 2015 as many as 110 people from stage I – III, the researchers are interested to doing therapy using warm water with a mixture of salt and lemon grass to lower blood pressure. The purpose of this study was to determine the effect between soaking feet using warm water with a mixture of salt and cymbopogon nardus l. rendle with reduction of blood pressure in patients with hypertension in region Podorejo RW 8 Ngaliyan. Quantitative research manifold quasi experiment with design Time Series Design Without Control. Sampling technique used Purposive Sampling counted 80 people. Data obtained by statistical test using Wilcoxon test. Based on Wilcoxon test showed Z = -8,127 (sistolik) Z = -5,587 (diastolik) and ρ value = 0,000 with α = 0,05. Where ρ value 0,000 < 0,05, so that H0 rejected Ha be accepted. There is any any effect of soaking feet using warm water with a mixture of salt and lemon grass toward reduction of blood pressure in patients with hypertension in region RW 8 Podorejo Ngaliyan. Nurses are expected to be used as a therapy to help people with hypertension to lower blood pressure.